The Effect of Application of Make A Match Method With The Assistance of Media Wordwall on Student Interest in Islamic Religious Education Subjects in Elementary School - Tastin, Tastin; Sari, Winni Herliana; Syarifuddin, Ahmad; Hamzah, Amir; Nurlaeli, Nurlaeli (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to determine the effect of the make a match method assisted by wordwall media on students' learning interest in Islamic Religious Education subjects. This type of research is quasi-experimental with a quantitative approach. The sample in this study were 37 grade IV students. Data collection techniques were carried out using questionnaires, observation, and documentation. The data analysis technique used is simple linear regression. Research using validity test, reliability test, and hypothesis testing. The results of the study included students' interest in learning in the control class which did not apply the make a match method assisted by wordwall media, which showed a significant increase in student interest in learning. This is evidenced by the data obtained from distributing questionnaires to the control class. The increase in student learning interest in the control class which was initially 59.62 became 67. Then for student learning interest in the Experiment class which in its application used the make a match method assisted by wordwall media, showed a very significant increase in student learning interest. This is evidenced by the data obtained from distributing questionnaires to the experimental class. There was an increase in student learning interest in the experimental class, which was originally 60.19 to 80.47. Based on this, it is known that the make a match method assisted by wordwall media has an effect on the learning interest of fourth grade students from the results of simple regression test calculations which show a significance value of 0.000 <0.05.